Investigation of the reach and effectiveness of a mentoring program for youth receiving outpatient mental health services. (August 2018) - DuBois, David L.; Herrera, Carla; Higley, Elizabeth
Abstract: This research investigated the reach and effectiveness of Great Life Mentoring (GLM), a program for youth receiving outpatient mental health services in which community volunteers are paired with participating youth in one-to-one mentoring relationships. Study participants included 91 youth served by GLM over an approximately 15-year period and a randomly selected sample of 400 youth who received mental health care from the same agency but did not participate in GLM. Although youth involved in GLM were similar to their peers on most assessed characteristics, they also differed in some ways at initiation of treatment services. For example, GLM-served youth were younger, more likely to be from a very-low-income family, and more likely to have a primary diagnosis of attention deficit/hyperactivity disorder (ADHD) and a secondary diagnosis. The average duration of the mentoring relationships established for the 91 GLM youth, including both those that had ended and those that were still ongoing, was about three years ( M  = 35.49 months), with only a small percentage (7.7%) having ended in less than one year. Longer-term mentoring relationships were predicted by being from a low-income family (rather than a very-low-income family), having a mentor with a higher education level, and not having a primary diagnosis of ADHD. When comparing change over time on clinician-ratings on the Children's Global Assessment of Functioning for propensity-score-matched groups of GLM ( n  = 66) and non-GLM ( n  = 66) youth, the GLM youth showed significantly more favorable change than their matched counterparts after the point in time at which they were paired with a mentor through the program. Relative to their matched counterparts, GLM youth also were less likely to have an unplanned and client-initiated ending of treatment (33.9% vs. 56.3%) and more likely to have a planned ending of treatment (32.3% vs. 18.8%). Highlights: Evaluated the reach and effectiveness of Great Life Mentoring (GLM), a program for youth in outpatient mental health care. Clinician intake ratings of functioning for youth in GLM were similar to those of other youth served by the same agency. Mentoring relationships for youth in GLM lasted, on average, approximately 3 years. GLM youth had more positive change in clinician ratings of functioning relative to youth in a matched comparison group. GLM youth also were more likely than comparison youth to have a planned ending to their mental health treatment.